Resonancia Magnética de Hígado - Csendes G., Paula; Sanhueza S., Álvaro; Aldana V., Hernán (Revista Hospital Clínico Universidad de Chile, 2006)
The development of the magnetic resonance has allowed to study and characterize the hepatic diseases with greater sensitivityand specifi city than the other methods of study, avoiding the risks of ionizing radiation. We discuss the main indications of themagnetic resonance for the study of the benign and malign lesions of the liver, like hemangioma, focal nodular hiperplasia,adenoma, hepatocarcinoma, colangiocarcinoma and metastasis, also the utility of the magnetic resonance in the diagnosis ofthe diffuse hepatic disease.